Coping Strategies and Associations With Depression Among 12- to 15-Year-Old Norwegian Adolescents Involved in Bullying. Issue 4 (April 2016) - Undheim, Anne Mari; Wallander, Jan; Sund, Anne Mari
Abstract : Abstract: The aim of this study was to examine coping styles among young adolescents involved in bullying, both as victims or aggressors, and the relationships between coping styles and depressive symptom levels. The possible moderating and mediating roles of coping in the relationships between bullying involvement and depression are also investigated. A representative community sample of 2464 adolescents was assessed. Coping styles were measured by the Coping Inventory for Stressful Situations. Depressive symptoms were assessed by the Mood and Feelings Questionnaire. Analysis of variance and standard linear regression methods were applied. Adolescents being bullied or being aggressive toward others both showed more emotional coping than did noninvolved adolescents ( p < 0.001). Being bullied and high emotional, low task, and high avoidant coping styles were independently related to more depressive symptoms. The association between being bullied and depressive symptoms was both moderated and partially mediated by emotional coping.